(untitled) (Indian Journal of Animal Production and Management, 2024)
This study aims to investigate time spent on eating, rumination, and resting during the three days before, the day of, and three days after, estrus in suckled buffaloes. Two experiments were conducted with 24 buffaloes each. In Experiment 1, buffaloes were divided into three groups (n=8): NC (No Cow-Calf and Cow-Bull Contact), RC (Restricted Cow-Calf and Fenceline Cow-Bull Contact), and FC (Fenceline Cow-Calf and Cow Bull Contact). In Experiment 2 (n=12), buffaloes were divided into two groups: RC (Restricted Cow Calf and No Cow-Bull Contact) and FC (Fenceline Cow-Calf and Direct Cow-Bull Contact). The data on mean frequencies of the time spent on eating, rumination and resting behaviours were compared between treatments on 3 days before oestrus (d -3, -2, -1), the day of oestrus (d 0) and 3 days after oestrus (d +1, +2, +3), using Duncan’s Multiple Range test and a one-way ANOVA. There was a significant effect of time (P<0.01), group (P<0.01), and their interaction (P<0.01) on time spent on eating, rumination, and resting in both experiments. In Experiment 1, the mean time spent on feeding was significantly higher (P<0.05) in the FC group compared to RC and NC on day -2 of estrus. Time spent on rumination was significantly higher (P<0.05) in RC and FC groups compared to NC on days -2, -1, and +1 of estrus. Resting time was statistically similar among the three groups on the day of estrus. In Experiment 2, resting time was significantly different (P<0.01) between RC and FC groups on days -2, -1, and +2 of estrus, but not on days -3, 0, +1, and +3. In conclusion, changes in feeding, rumination, and resting behaviors are significant indicators for detecting estrus in buffaloes. Fenceline and direct contact with bulls enhance these behavioral changes, providing a practical approach to estrus detection through monitoring of these specific activities.